Selective pericellular hydrogelation by the overexpression of an enzyme and a membrane receptor. Issue 29 (17th July 2019) - Wang, Yuhan; Zhan, Jie; Chen, Yumiao; Ai, Sifan; Li, Liantao; Wang, Ling; Shi, Yang; Zheng, Junnian; Yang, Zhimou
Abstract : A strategy for the selectively pericellular hydrogelation via a mechanism that involves alkaline phosphatase expressed outside the cells and CCK2R expressed in the cell membrane. Abstract : The selective formation of nanomedicines around cancer cells is very important for cancer therapy because it increases the inhibitory capacity and decreases the systemic toxicity. However, successful examples are rare. Taking advantage of the overexpression of both the enzyme alkaline phosphatase (ALP) and the cell membrane receptor (CCK2R), we demonstrated in this study the selective formation of supramolecular nanofibers and hydrogels in the pericellular space of two cancer cell lines (HeLa and HepG2 cells). Both cell lines showed high expression levels of extracellular ALP and membrane-bound CCK2R. ALP efficiently converted Comp. 1 to a self-assembling molecule ( Comp. 2 ). Comp. 2 interacted with CCK2R, thereby facilitating the self-assembly and formation of hydrogels around the cancer cells. The selective pericellular hydrogelations efficiently inhibited cancer cells. Pericellular hydrogelation around cancer cells is a promising strategy to control the formation of nanomedicines spatiotemporally in cellular microenvironments for cancer therapy and diagnostics.